BIMBINGAN PRA NIKAH DENGAN KONSEP KAFA’AH PADA PASANGAN TNI AL DI MAKO LANAL SEMARANG - Assharofi, Faiz Abdul Majid; Mintarsih, Widayat (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research is based on the concept of kafa'ah as pre-marital guidance material for Indonesian Navy couples at LANAL Semarang. The importance of understanding the concept of kafa'ah for both prospective partners is very helpful in family life between the two. This type of research is descriptive qualitative with a phenomenological approach. The research results show that the concept of kafa'ah has a central role in the pre-marital guidance process at MAKO LANAL Semarang. In the context of marriage, there are 5 (five) kafa'ah criteria: First, religious criteria. Although the views of the interviewees varied, the majority emphasized the importance of religious compatibility as the main priority, with an emphasis on communication and honesty. Second, the criteria of lineage and moral suitability are also considered important in choosing a partner. Third, suitability for work or profession is also considered, even though in a military environment, hierarchical rules are still a consideration. Fourth, the independence criteria for prospective Indonesian Navy spouses emphasize the importance of compatibility in all aspects of life, communication and management. Fifth, not being disabled is also emphasized, especially in the context of institutions such as the Indonesian Navy. The results of this research show that the concept of kafa'ah in the context of marriage has significant implications for the choice of life partner in society, especially in the Indonesian Navy community. The approach using the kafa'ah concept was welcomed by prospective brides and grooms, who realized the importance of choosing a partner who is in accordance with the values and principles upheld in married life.